Moral Education: Too Little, Too Late? - McClelland, Richard T. (Christian scholar's review, 2010)
Colleges and universities often expect their curriculum to engage with the moral formation of their students. In this essay Richard T. McClelland notes that four scientific arguments converge to suggest that this project is unlikely to succeed: the evolutionary origins of human moral systems, the ontogeny of the average human brain, closing the gap between our dispositions to behave and our actual behavior, and the origin of most moral judgments in automatic processes operating on culturally transmitted intuitions that are not subject to change by traditional curricular methods. Furthermore, mechanisms for changing intuitions risk either alienation of the institution from the cultural surround or fraudulent identification with it. Mr. McClelland is Associate Professor of Philosophy at Gonzaga University.